História e economia: Caio Prado Júnior (1929-1945) - Santos, Rodrigo Cesar De Araujo [UNIFESP] (2019)
In this work we analyze the ways in which Caio Prado Júnior historicizes the concepts of political economy and relates history and economy in his historiographical production, problematizing the dialogue and articulations between history and theory, between the reconstitution and the conceptualization of the past. We investigate, therefore, the mediations that the author establishes between the narration of events (territory of diachrony, indetermination and singularity) and the explanation of structures (territory of synchrony, determination and universality). We hypothesize that it is in the dynamic relation between conceptualization (generalization) and narrative (particularization) that we can find the way to comprehend Caiopradean thought in its totality. In this sense, we analyze Caio Prado Júnior’s work with special attention to the concepts of production and circulation present in his historiography. Considering that our research object is delimited as a particular aspect of the author's thought and that Caio Prado Júnior’s historiographical production is linked to the experiences he lived at the time of its elaboration, we understand these concepts of political economy as part of the broader framework of economic thought and the historiography of his time and seek to relate the author's biography to his historical narrative. Thus, we intend to contribute to deepen the knowledge about the theory of history mobilized by the author, the mediations he made between the temporalities of history and the tensions between history and theory in his historiographical work.